1974
DOI: 10.1126/science.186.4169.1120
|View full text |Cite
|
Sign up to set email alerts
|

Lead Contamination around Secondary Smelters: Estimation of Dispersal and Accumulation by Humans

Abstract: A high rate of lead fallout around two secondary lead smelters originated mainly from episodal large-particulate emissions from low-level fugitive sources rather than from stack fumes. The lead content of dustfall, and consequently of soil, vegetation, and outdoor dust, decreased exponentially with distance from the two smelters. Between 13 and 30 percent of the children living in the contaminated areas had absorbed excessive amounts of lead (more than 40 micrograms per 100 milliliters of blood and more than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
6

Year Published

1979
1979
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(47 citation statements)
references
References 11 publications
1
39
1
6
Order By: Relevance
“…Smelters account for only a small fraction of total airborne emissions, but they can emit large amounts of lead from their stacks and through fugitive emissions and can produce intense local accumulations of lead. This localized environmental contamination can be refl ected in elevated blood lead levels in nearby residents (13,14). Automotive lead emissions from the combustion of alkyl lead in gasoline have been slightly reduced since the introduction in 1975 of catalytic con verters; the converters require lead-free fuel.…”
Section: Environmental Pathwaysmentioning
confidence: 99%
“…Smelters account for only a small fraction of total airborne emissions, but they can emit large amounts of lead from their stacks and through fugitive emissions and can produce intense local accumulations of lead. This localized environmental contamination can be refl ected in elevated blood lead levels in nearby residents (13,14). Automotive lead emissions from the combustion of alkyl lead in gasoline have been slightly reduced since the introduction in 1975 of catalytic con verters; the converters require lead-free fuel.…”
Section: Environmental Pathwaysmentioning
confidence: 99%
“…Concentrations of copper, cadmium and zinc discharged from smelting and other metal processing works are shown to follow an exponential decrease with distance from the point source (Roberts et al, 1974;Gale and Wixson, 1979;Farago and O'Connell, 1983;Miller and McFee, 1983;Wachowska-Serwatka and Serwatka, 1984;Hunter et al, 1987;Alloway, 1990;Storm et al, 1994). Although Hunter et al (1987) have shown that cadmium and copper concentrations in surface soils decline to control levels within 2-3 km of the works boundary, most of the marked retention of aerially deposited metals is at the point source and 1 km distance from the source.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have calculated slope factors to describe the association between environmental measures of lead in soil and dust in and around the home and the blood lead levels of children (Barltrop et al, 1974;Roberts et al, 1974;Baker et al, 1977;Yankel et al, 1977;Stark et al, 1982;Angle et al, 1984;Reagan and Silbergeld, 1989). However, there is considerable variability among these slope factor estimates (ATSDR, 1999;Lewin et al, 1999).…”
Section: Introductionmentioning
confidence: 99%